Intervalling-Effect Bias and Competition Policy - Fotis, Panagiotis N.; Pekka-Oikonomou, Victoria; Polemis, Michael L. (Journal of Reviews on Global Economics, 2015)
The purpose of this paper is twofold. First, it aims to investigate whether the security’s systematic risk beta estimates change as the infrequent trading phenomenon appears. Second, it attempts to provide useful insight on the impact of mergers and acquisitions on competition policy. For this reason, we employ the models of Scholes and Williams (1977), Dimson (1979), Cohen et al. (1983a) and Maynes and Rumsey (1993) on a small stock exchange with thickly infrequent trading stocks. The empirical results reveal that for some securities the models employed by Scholes and Williams (1977) and Cohen et al. (1983a) improve the biasness of the Ordinary Least Squares Market Model (Maynes and Rumsey, 1993). We argue that competitors gain while merged entities loose or at least do not gain from the clearness of the investigated mergers.